Risk Factor Analysis and Microbial Etiology of Surgical Site Infections following Lower Segment Caesarean Section. (28th August 2013) - De, Devjani; Saxena, Sonal; Mehta, Geeta; Yadav, Reena; Dutta, Renu
Abstract : Background . Lower segment caesarean section (LSCS) is a common mode of delivery now and surgical site infection is the second most common infectious complication in these patients. This study was planned with this background to have a comprehensive approach to SSI following LSCS. Methods . 500 consecutive patients undergoing LSCS, irrespective of indication, were studied. A questionnaire was developed to assess the risk factors associated with development of SSI. All patients were followed up from day one of surgery till discharge and then up till the postoperative day 30 after discharge. Results . SSI was identified in 121 (24.2%) out of 500 patients. In all age groups, Gram-negative bacilli were the commonest finding. The commonest isolate was Acinetobacter species (32.03%) followed by Staphylococcus aureus and coagulase negative Staphylococcus (21.09%). 23.8% of Staphylococcus aureus strains were MRSA. By multivariate logistic regression premature rupture of membrane (PROM), antibiotics given earlier than 2 hours and increased duration of stay in the hospital were found to be significant. Conclusions . A proper assessment of risk factors that predispose to SSI and their modification may help in reduction of SSI rates. Also, frequent antimicrobial audit and qualitative research could give an insight into the current antibiotic prescription practices and the factors affecting these practices.